Electro-optical Analysis of the Effects of Bacteriophages on Microbial Cells - O. I. Guliy; O. A. Karavaeva; O. S. Larionova; S. V. Larionov; L. G. Lovtsova; K. Yu. Uskov; V. D. Bunin (Антибиотики и Химиотерапия)
The effect of the ФАb-Sр7 bacteriophage on the change in the electro-optical (EO) parameters of cell suspensions with respect to 14 strains of bacteria of the genus Azospirillum, 2 strains of the genus Niveispirillum, 2 strains of Escherichia coli, and 2 strains of Pseudomonas putida, as well as Acinetobacter and Nitrospirillum cells was studied. It is shown that the EO analyzer makes it possible to differentiate situations when bacterial cells interact with a specific bacteriophage from control experiments with no such interaction.The registration of a microbial cell infection with a bacteriophage by the EO analysis method serves as an informative parameter of the presence or absence of cell sensitivity to the bacteriophage studied. The obtained results make it possible to determine the criterion for a specific interaction, which consists of a change in the magnitude of the optical signal by not less than ~10% when a certain amount of bacteriophages is added to the suspension of microbial cells.The results are of interest from a practical point of view since they can be used to create a method for rapid assessment of the effects of bacteriophages on microbial cells.